Effective delivery of bone morphogenetic protein 2 gene using chitosan–polyethylenimine nanoparticle to promote bone formation. Issue 41 (6th April 2016) - Zhao, Liang; Zhang, Kai; Bu, Wenhuan; Xu, Xiaowei; Jin, Han; Chang, Bei; Wang, Banchao; Sun, Yingjian; Yang, Bai; Zheng, Changyu; Sun, Hongchen
Abstract : Treating bone defects is still a challenge in clinical practice. Abstract : Treating bone defects is still a challenge in clinical practice. Recently, researchers used human bone morphogenetic protein 2 gene (hBMP-2) to induce osteoblast differentiation and promote new bone formation. However, an efficient way to deliver hBMP-2 still needs to be created. In this study, we evaluated whether chitosan–polyethylenimine (CS–PEI) nanoparticle could effectively deliver hBMP-2 locally with lower or no toxicity and promote osteoblast differentiation and new bone formation in vitro and in vivo . Data demonstrated that the synthesized CS–PEI/hBMP-2 nanoparticle at a W/W ratio of 20 to 1, which was the smallest size (162 nm) and highest zeta potential (24 mV), effectively transfected MC3T3-E1 cells without cytotoxicity in vitro, and had the ability to promote cell proliferation. Interestingly, the CS–PEI/hBMP-2 nanoparticle eliminated disadvantages of lower transfection efficiency from chitosan and cytotoxicity from PEI. RT-QPCR data showed that MC3T3-E1 cells treated with CS–PEI/hBMP-2 nanoparticle dramatically expressed higher levels of BMP-2 and significantly increased gene expressions of Col1 on days 3 and 14, Sp7 on days 3, 7, and 14, and ALP on day 14. Alizarin red staining demonstrated that CS–PEI/hBMP-2 nanoparticle-treated MC3T3-E1 cells significantly increased cell mineralization. These in vitro data suggest that the CS–PEI/hBMP-2 nanoparticle can effectively induce osteogenic differentiation of MC3T3-E1 cells in vitro . Western blot analysis further demonstrated that transgene BMP-2 indeed phosphorylated Smad1/5/8, which indicates that CS–PEI/hBMP-2 nanoparticle affects cell differentiation through a BMP-2 signal pathway. Importantly, in vivo data showed that CS–PEI/hBMP-2 nanoparticle clearly promoted new bone formation at the bone defect area 12 weeks post-implantation. This indicates that synthesized CS–PEI/hBMP-2 nanoparticle has the potential to become a useful therapeutic vector for bone defect treatment with further modification.